Pengaruh Profitabilitas, Ukuran Perusahaan Dan Likuiditas Terhadap Kebijakan Hutang Perusahaan Manufaktur - Dwi Putri Novitasari, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This study aims to analize the influence of profitability, firm size and liquidity to debt to equity ratio in manufacturing companies who were listed on Indonesia Stock Exchange between 2015-2017. The sample wich included criteria is 65 companies, the sample was taken using the method of purposive sampling and those meeting the selection criteria were also taken. The statistics method used was multiplied analysis linear regression, with hypotheses testing of statistic t and F test, and with analysis helped by SPSS 20 program. The result of this research are profitability, firm size and liquidity affect debt policy. The result of this research shows partially that profitability did not affect the debt policy. Firm size did not affect the debt policy, and liquidity had a negative and significance affect on debt policy.